Antioxidants and Male Infertility - Ricardo Silva; David F. Carrageta; Marco G. Alves; Branca M. Silva; Pedro F. Oliveira (MDPI AG, 2022)
Oxidative stress has been associated with decreased sperm quality and male infertility [...]